Rating of LQ-45 stock index performance credibility in Indonesia Stock Exchange - Tona Aurora Lubis; Ade Octavia; Widyanti Fitri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to analyze stock performance credibility using the Capital Asset Pricing Model (CAPM) method, the Arbitrage Pricing Theory (APT) method, the Fama-French Three-Factor Model (FFTFM), and the 2013-2017 LQ-45 Stock Performance rating. The technique used for sampling is purposive sampling. The samples in this study are 23 companies. The results show that the CAPM model is more accurate in stock credibility assessment than the APT model and the FFTFM.